Polydopamine Coating To Stabilize a Free-Standing Lipid Bilayer for Channel Sensing - Neveshkin, Alexander (Langmuir : the ACS journal of surfaces and colloids, 2017)
An appropriate method to study the function of membrane channels is to insert them into free-standing lipid bilayers and to record the ion conductance across the membrane. The insulating property of a free-standing lipid bilayer versus the single-channel conductivity provides sufficient sensitivity to detect minor changes in the pathway of ions along the channel. A potential application is to use membrane channels as label-free sensors for molecules, with DNA sequencing as its most prominent application. However, the inherent instability of free-standing bilayers limits broader use as a biosensor. Here we report on a possible stabilization of free-standing lipid bilayers using polydopamine deposition from dopamine-containing solutions in the presence of an oxidant. This stabilization treatment can be initiated after protein reconstitution and is compatible with most reconstitution protocols